Serum interleukin-6, interleukin-8, and interleukin-1 receptor antagonist levels in South Indian fibromyalgia patients and its correlation with disease severity - Sandeep Surendran; C B Mithun; Vishnu S Chandran; Suma Balan; Arun Tiwari (Indian Journal of Rheumatology)
Background: Fibromyalgia is a chronic pain syndrome characterized by widespread diffuse pain and multiple tender points along with sleep disturbances, fatigue, and psychological distress. Cytokines have been proposed to play an important role in the pathogenesis of fibromyalgia. Different studies, mainly done in the Western population, have shown dysregulated cytokines in fibromyalgia patients. This study was aimed to analyze the serum cytokine patterns of interleukin-1 receptor antagonist (IL-1Ra), interleukin-8 (IL-8), and interleukin-6 (IL-6) in Indian females with fibromyalgia and its correlation with the disease severity. Materials and Methods: This single-center cross-sectional study compared the serum cytokines levels (IL-6, IL-8, and IL-1Ra) of 21 females fulfilling 2016 modification of the 2010/11 American College of Rheumatology fibromyalgia criteria and without co-existent major depressive or inflammatory diseases; with 20 age- and sex-matched controls. The outcome measures used to measure disease activity were visual analog scale pain, fibromyalgia impact questionnaire-revised, brief pain inventory pain scores, and SF-36 health survey. Statistical tests used were the Kolmogorov–Smirnov test of normality, Mann–Whitney's test, Chi-square tests, Spearman rank order, and Benjamini–Hochberg correlation. Results: Serum IL1-Ra levels were significantly lower in fibromyalgia patients, median 226.90 pg/ml (interquartile range [IQR] 476.95) than the healthy controls, median 778.80 pg/ml (IQR 721) (P < 0.05). However, there was no statistical difference in the levels of IL-8 and IL-6 between patients and the control group. The analysis for the correlation between cytokine and outcome measures failed to show any statistically significant correlation. Conclusion: Fibromyalgia patients in our study had lower serum IL-1Ra level, whereas IL-8 and IL-6 levels were normal. When compared with western studies, these contrasting results suggest a heterogeneous cytokine profile of fibromyalgia patients in different ethnic groups.